Butte Paper - Cement Materials and the Manufacture of Portland Cement in Montana - W. H. Andrews (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1914)
The constantly increasing consumption of Portland cement in the State makes the above subject of particular interest at this time. The increasing demand is due to the rapid settling of the country and the fact that new uses are being found frequently for the above named commercial article. The industry is one that is bound to grow as the population increases, and this being the case it may be well at this time to consider briefly the matter of the chemical and physical composition of proper raw materials. A cement mixture is one that contains approximately 75 per cent, carbonate of lime, 15 per cent. silica, and 5 to 7 per cent. alumina and iron oxides; the other elements being magnesium carbonate and mall quantities of the rarer elements generally associated with limestone deposits. It can be readily seen from the above composition that it is possible to build up this mixture from a number of different materials. First.—A rock high in carbonate of lime can be mixed with clay or shale in such proportions as to bring about the desired composition ; the chief difficulty in the building up of such a mixture is that it is hard to find a clay or shale in which the silica-alumina ratio lies between 4 to 1 and 3 to 1 and at the same time shows physical characteristics which will make certain its adaptability to the practical manufacture of Portland cement. Very often clays or shales are found which are right chemically but contain large quantities of grit or free silica. Such clays or shale must be ground to extreme fineness in the mixture in order to make the silica and alumina combine with the lime when the mixture is burned. On the other hand, clays or hales are often found that have the proper physical characteristics but in which the amount of alumina is too great. Second.—A mixture can be built up of different limestones some of which run above the 75 per cent. requirement and others below;